1998
DOI: 10.1074/jbc.273.17.10302
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of a Protein Disulfide Catalytic System

Abstract: Disulfide bonds are important for the structure and stability of many proteins. In prokaryotes their formation is catalyzed by the Dsb proteins. The DsbA protein acts as a direct donor of disulfides to newly synthesized periplasmic proteins. Genetic evidence suggests that a second protein called DsbB acts to specifically reoxidize DsbA. Here we demonstrate the direct reoxidation of DsbA by DsbB. We have developed a fluorescence assay that allows us to directly follow the reoxidation of DsbA. We show that membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
95
0
5

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 26 publications
4
95
0
5
Order By: Relevance
“…Cells were grown at 37°C on L-medium containing 100 g/ml of ampicillin, induced with 10 M isopropyl-1-thio-␤-D-galactopyranoside at a turbidity of Klett unit 60, and harvested at 4 h after the induction. DsbB and its derivatives were purified essentially as described by Bader et al (13,24). UV spectrum measurements after reduction with sodium borohydride (14) indicated that the purified preparations of DsbB contained ϳ0.5 mol equivalent of endogenously bound UQ.…”
Section: Methodsmentioning
confidence: 99%
“…Cells were grown at 37°C on L-medium containing 100 g/ml of ampicillin, induced with 10 M isopropyl-1-thio-␤-D-galactopyranoside at a turbidity of Klett unit 60, and harvested at 4 h after the induction. DsbB and its derivatives were purified essentially as described by Bader et al (13,24). UV spectrum measurements after reduction with sodium borohydride (14) indicated that the purified preparations of DsbB contained ϳ0.5 mol equivalent of endogenously bound UQ.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidation of the Reduced Variants by DsbB in Vitro-Membranes containing DsbB, ubiquinone, and terminal oxidases were prepared from E. coli JCB819 cells overexpressing DsbB as described (3,35). The DsbB-catalyzed oxidation of reduced DsbA was followed by the decrease in specific DsbA fluorescence at 330 nm (excitation at 280 nm).…”
Section: Methodsmentioning
confidence: 99%
“…DsbA-mediated disulfide bond formation in the periplasm involves oxidation of reduced, newly translocated substrate polypeptides by DsbA, followed by reoxidation of DsbA by the inner membrane protein DsbB. DsbB is in turn reoxidized by molecular oxygen through ubiquinone and terminal cytochrome oxidases (3,4).…”
mentioning
confidence: 99%
“…For kinetic studies, oxidation of DsbA was determined by the decrease in DsbA fluorescence (25) essentially as described by Bader et al (26). The initial velocity of the reaction was determined from the initial slope of the fluorescence change at 330 nm using a Hitachi F-4500 fluorescence spectrophotometer.…”
Section: Determination Of In Vivo Redoxmentioning
confidence: 99%